Transcription Factors Sox8 and Sox10 Contribute with Different Importance to the Maintenance of Mature Oligodendrocytes - Jörg, Lisa Mirja; Schlötzer-Schrehardt, Ursula; Lefebvre, Véronique; Sock, Elisabeth; Wegner, Michael (International Journal of Molecular Sciences, 2024)
Myelin-forming oligodendrocytes in the vertebrate nervous system co-express the transcription factor Sox10 and its paralog Sox8. While Sox10 plays crucial roles throughout all stages of oligodendrocyte development, including terminal differentiation, the loss of Sox8 results in only mild and transient perturbations. Here, we aimed to elucidate the roles and interrelationships of these transcription factors in fully differentiated oligodendrocytes and myelin maintenance in adults. For that purpose, we conducted targeted deletions of Sox10, Sox8, or both in the brains of two-month-old mice. Three weeks post-deletion, none of the resulting mouse mutants exhibited significant alterations in oligodendrocyte numbers, myelin sheath counts, myelin ultrastructure, or myelin protein levels in the corpus callosum, despite efficient gene inactivation. However, differences were observed in the myelin gene expression in mice with Sox10 or combined Sox8/Sox10 deletion. RNA-sequencing analysis on dissected corpus callosum confirmed substantial alterations in the oligodendrocyte expression profile in mice with combined deletion and more subtle changes in mice with Sox10 deletion alone. Notably, Sox8 deletion did not affect any aspects of the expression profile related to the differentiated state of oligodendrocytes or myelin integrity. These findings extend our understanding of the roles of Sox8 and Sox10 in oligodendrocytes into adulthood and have important implications for the functional relationship between the paralogs and the underlying molecular mechanisms.
CRIS-Team Scopus Importer:2024-09-06
Keywords: functional redundancy; glia; myelin; Sox proteins; transcriptional control